Potential Serological Misdiagnosis of Barmah Forest Virus and Ross River Virus Diseases as Chikungunya Virus Infections in Australia: Comparison of ELISA with Neutralization Assay Results - Joanne Kizu; Melissa Graham; Wenjun Liu (Viruses, 2024)
To evaluate the frequency of errors in the diagnosis of medical laboratory-diagnosed Chikungunya virus (CHIKV) infections in Australia, we studied 42 laboratory-diagnosed CHIKV serum samples from one Queensland medical laboratory by ELISA IgG/IgM and measured the specific neutralization antibodies (Nab) against Barmah Forest virus (BFV), CHIKV and Ross River virus (RRV). The sero-positivity rates for the sera were as follows: anti-BFV IgG+ 19% (8/42), IgM+ 2.4% (1/42) and Nab+ 16.7% (7/42); anti-CHIKV IgG+ 90.5% (38/42), IgM+ 21.4% (9/42) and Nab+ 90.5% (38/42); anti-RRV IgG+ 88.1% (37/42), IgM+ 28.6% (12/42) and Nab+ 83.2% (35/42), respectively. Among the samples with multiple antibody positivity, 2.4% (1/42) showed triple ELISA IgM+, and 14.3% (6/42) exhibited double IgM RRV+CHIKV+; 9.5% (4/42) showed triple IgG+, 76.2% (32/42) displayed double IgG RRV+CHIKV+, 4.8% (2/42) showed IgG BFV+RRV+ and 4.8% (2/42) showed IgG BFV++CHIKV+; and 9.5% (4/42) showed triple Nab+ and 69% (29/42) exhibited double Nab RRV+CHIKV+, respectively. Our analysis of the single-virus infection control Nab results suggested no cross-neutralization between RRV and BFV, and only mild cross-neutralization between CHIKV and RRV, BFV and CHIKV, all with a ≥4-fold Nab titre ratio difference between the true virus infection and cross-reactivity counterpart virus. Subsequently, we re-diagnosed these 42 patients as 1 BFV+, 8 CHIKV+ and 23 RRV+ single-virus infections, along with five RRV+/BFV+ and four RRV+/CHIKV+ double infections, and one possible RRV+/BFV+ or RRV+CHIKV+, respectively. These findings suggests that a substantial proportion of medically attended RRV and BFV infections were misdiagnosed as CHIKV infections, highlighting the imperative need for diagnostic laboratory tests capable of distinguishing between CHIKV infections and actively co-circulating RRV and BFV. For a correct diagnosis, it is crucial to consider reliable diagnostic methods such as the neutralization assay to exclude RRV and BFV.